EFFECTIVENESS OF LAMPUNG PROVINCIAL INSPECTORATE IN STRENGTHENING REGIONAL FINANCIAL ACCOUNTABILITY - Muhammad Andi Timor Pratama; Ida Farida (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes the effectiveness of the Lampung Provincial Inspectorate in strengthening the accountability of regional financial management and identifies the factors that support or constrain its performance. A qualitative descriptive case-study design was applied at the Lampung Provincial Inspectorate. Data were obtained through in-depth interviews with structural and functional officials and staff, direct observation, and analysis of official documents, including annual supervision programs, audit reports, standard operating procedures, and relevant regulations. Data credibility was established through source, method, and time triangulation as well as member checking, while analysis followed data reduction, data display, and conclusion verification. The findings show that internal supervision is implemented through an integrated cycle of risk-based planning, audit and review execution, evidence-based reporting, verification of recommendation follow-up, and continuous evaluation. This cycle encourages regulatory compliance and improves financial accountability. Evaluation and strengthening of internal control are the main supporting factors. However, delayed and insufficiently systematic reports, uneven responsiveness of regional agencies, high auditor workloads, weak inter-unit coordination, and limited use of supervisory information systems reduce the speed and impact of follow-up. The Inspectorate is therefore effective, but its performance still requires institutional and technological reinforcement.